Formwork for concrete structures - Peurifoy, R. L. (Robert Leroy), 1902-1995.; Oberlender, Garold D. (New York : McGraw-Hill, 2011)
'Formwork for Concrete Structures, Fourth Edition, provides current information on designing and building formwork and temporary structures during the construction process. Developed with the latest structural design recommendations by the National Design Specification (NDS 2005), the book covers recent advances in materials, money- and energy-saving strategies, safety guidelines, OSHA regulations, and dimensional tolerances. Up-to-date sample problems illustrate practical applications for calculating loads and stresses. This comprehensive manual also includes new summary tables and equations and a directory of suppliers.'--Publisher's description.
Includes bibliographical references and index.
Keywords: Concrete construction -- Formwork